Countering anti-vaccination trends and changing online opinion. (13th November 2019) - Signorelli, C; Odone, A
Abstract: We reported the case study of Professor Roberto Burioni, a medical microbiologist and virologist who, in 2015, started a personal social media campaign to contrast anti-vaccinists, using Facebook and other social media to disseminate the science behind vaccines and disseminating scientific data to refute rumors about their dangers. With over 500, 000 people following his Facebook profile, Burioni has become a popular role model and influencer in the field of vaccines, openly criticizing vaccines' refusers and fighting fake news. He used a rather aggressive tone, claiming they are ignorant and that "science is not a matter of democracy". Although it is methodologically difficult to quantitatively estimate the so-called 'Burioni effect' in influencing vaccines' confidence, we report a drastic rebalance of the number of Italian social media pages supporting vaccines after 2015 suggesting his action on the web has been successful. In fact in 2015 Fakebook pages with the highest amount of contacts were anti-vax, while in 2018 pages with the highest number of contacts were those of supporting the scientific rationale of immunization. We are studying this phenomenon inside a project considering areas of Italy with high prevalence of no-vaxxers and hesitants.